IMPLEMENTATION OF THE LIMITED LIABILITY COMPANY LEGAL DOCTRINE IN THE LIABILITY OF DIRECTORS IN INDONESIA - Syarifah Aisyah; Norhalisa Nabella; Alya Ahda Nadhirah; Muhamad Rahmani Abduh (JSE: Jurnal Sharia Economica, 2026)
This study examines the implementation of key doctrines in corporate law related to directors’ liability in limited liability companies in Indonesia. The doctrines analyzed include Piercing the Corporate Veil, Business Judgment Rule, Ultra Vires, and Fiduciary Duty. This research employs a normative legal method with statute, conceptual, and case approaches. Legal materials were collected through literature studies and analyzed qualitatively to understand the application of these doctrines in corporate legal practice in Indonesia.  The findings indicate that these doctrines play an important role in determining the limits of directors’ responsibilities in corporate management. The doctrine of Piercing the Corporate Veil allows courts to impose personal liability when the corporate entity is misused, as illustrated in the case involving PT Effem Foods Inc. The Business Judgment Rule provides legal protection for directors in making business decisions in good faith, as reflected in the case of PT Merpati Nusantara Airlines. The Ultra Vires doctrine emphasizes that corporate actions must remain within the scope of the company’s objectives, as shown in the PT Condato Grup Indonesia case. In addition, the Fiduciary Duty doctrine highlights directors’ obligations to act with due care and loyalty in managing the company, as seen in the PT Bakara Bumi Energi case.